Constructive Technology Assessment: Systematic Review and Future Study Needs - Rodríguez-Cardoso, Óscar Iván; Ballesteros-Ballesteros, Vladimir Alfonso; Romero-Ospina, Manuel Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Engineering, understood as the gathering of scientific and technological knowledge for innovation, creation, advancement and optimization of techniques, as well as a set of useful tools to meet social needs and solve technical problems of both individuals and the community, makes its main actors, engineers, key players in sustainable development and in the creation of alternatives that minimize the negative effects of technology on society. It is in this sense that technology assessment approaches should take importance among those who manage technology development and implementation policies. Generally, the undesirable effects of the intrusion of a new technology are acted upon when they already occur, and technology assessment is intended to anticipate the risk. This paper presents a bibliographic review of technology assessment, its approaches and future study needs. Based on an articulating axis that positions technological change and innovation as an imperative need for social development, an exhaustive review of related articles in specialized databases was carried out. The most important results of this work reveal that the field of technological assessment has been strongly inclined towards the health or sanitary sector; however, research is being developed in central engineering topics such as the development of nanotechnology, robotics, and the handling of big data, where the European model stands out as a reference for technological assessment processes due to its inclusive and democratic nature.